Syn-sedimentary Mafic Volcanics in the Eocene Coal-bearing Tanjung Formation, Senakin Peninsula, South Kalimantan (Borneo), Indonesia - Tim Allen Moore; Mike C. Friederich; Jessica Trofimovs; Ferian Anggara; D. Hendra Amijaya (Geological Agency, 2020)
DOI:10.17014/ijog.7.1.65-85Syn-sedimentary mafic volcanism has been identified within a rift setting (Eocene Tanjung Formation) in the Senakin Peninsula, southeast Kalimantan. Fine-grained, dark-grey basalt lava occurs and has prominent vertically oriented columnar jointing. Petrographically, the basalt is composed of small euhedral pyroxene, olivine, and lath-shaped plagioclase phenocrysts within a very fine-grained dark coloured groundmass. A volcaniclastic unit also occurs and in outcrop has sharp contacts with underlying and overlying sedimentary mudstone. The unit is composed of cm-scale clasts of fine-grained to glassy textured basalt with vesicles of varying size and abundance. Euhedral pyroxene phenocrysts are observed within the clasts, although some with overprinting alteration. Palagonite alteration on the margins of some clasts is noted and is indicative of mafic composition volcanic material that has come into contact with sea water. Presence of bivalve and coral fragments in sandstone and mudstone underlying the volcaniclastic unit indicates emplacement into a marine environment. Core description from 33 locations over an 18 km transect length show that both the basalt and volcaniclastic sediments are extensive throughout the east Senakin area. Lithological relationships and compositional similarities between the basalt and volcaniclastic sediment suggest they are related and were contemporaneous with sedimentation within the Tanjung Formation. It is proposed that the basalt unit is designated the Tanah Rata Basalt Member of the Tanjung Formation. If a wider distribution occurs for the volcaniclastic unit it is proposed that it is termed the Gumbil Volcaniclastic Member of the Tanjung Formation.